The relationship between the timing of lung surgery and postoperative pulmonary complications in patients after SARS-CoV-2 infection: a prospective cohort study - Yang, Dawei; Li, Min; Duan, Xianning; Ji, Fuhai; Zhang, Jianyou (Frontiers in Medicine, 2025)
BackgroundPatients with a positive test for SARS-CoV-2 prior to elective surgery early in the pandemic have an elevated risk of perioperative mortality and pulmonary complications. Post-SARS-CoV-2 infection, pulmonary sequelae persist beyond the acute stage, necessitating recovery periods spanning months or even longer. Our study aimed to explore the correlation between the timing of thoracoscopic lung surgery and postoperative pulmonary complications (PPCs) in patients with a history of SARS-CoV-2 infection.MethodsWe conducted a prospective cohort study, enrolling patients scheduled for elective thoracoscopic partial lung resection. Participants were categorized into two groups based on the duration since their SARS-CoV-2 infection: 5–10 weeks and 11–16 weeks. A total of 68 patients were included, with 34 in each group. The information about SARS-CoV-2 infection were collected; IL-6 and TNF-α levels at 2 h, 1 d, and 2 d after surgery and the WBC count and CRP level in blood at 1 d and 2 d after surgery were analyzed; and PPCs and length of hospitalization were recorded. A logistic regression model was employed to assess the relationship between the timing of lung surgery and PPCs in patients post SARS-CoV-2 infection.ResultsCompared with the 5-10-week group, in the 11-16-week group, the levels of IL-6 and TNF-α at 2 h, 1 d, and 2 d after surgery were significantly lower, the WBC count and CRP levels in blood at 1 d and 2 d after surgery were significantly lower, the numbers of PPCs and lung infections were significantly lower, and the length of hospitalization was significantly shorter. Multivariate logistic regression analysis revealed that the time interval from surgery to SARS-CoV-2 infection, persistent preoperative symptoms, preoperative difficulty breathing and WBC count at 1 d after surgery were independent risk factors for PPCs.ConclusionPatients infected with SARS-CoV-2 who underwent thoracoscopic lung surgery within 5 to 10 weeks after infection had a higher risk of PPCs than those who had surgery at 11 to 16 weeks post-infection.Clinical trial registrationhttps://clinicaltrials.gov/, ChiCTR2300071539.